2013
DOI: 10.1080/02508060.2013.830691
|View full text |Cite
|
Sign up to set email alerts
|

An introduction to the IBMR, a hydro-economic model for climate change impact assessment in Pakistan’s Indus River basin

Abstract: The Indus Basin Model Revised (IBMR) is a hydro-agro-economic optimization model for agricultural investment planning across Pakistan's Indus Basin provinces. This study describes an update and modification of the model-called IBMR-2012-that reflects the current agroeconomic conditions in Pakistan for the purpose of evaluating the impact of climate change on water allocation and food security. Results of hydro-climatic parameter sensitivity and basinwide and provincial level climate change impacts on crop prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 13 publications
0
25
0
Order By: Relevance
“…Reference [45] estimated the impact of these changes on the farming sector and concluded that climate variability could have a negative impact on food productivity and could cause food insecurity. In their research, the authors of Reference [46] used the revised Indus Basin Model (IBMR) to check the impact of climate change on water availability and food security in Pakistan and found out that Sindh is more vulnerable to climate variabilities than other provinces. The influence of CC on rice yield in light of several carbon dioxide emission scenarios was assessed by Reference [40].…”
Section: Introductionmentioning
confidence: 99%
“…Reference [45] estimated the impact of these changes on the farming sector and concluded that climate variability could have a negative impact on food productivity and could cause food insecurity. In their research, the authors of Reference [46] used the revised Indus Basin Model (IBMR) to check the impact of climate change on water availability and food security in Pakistan and found out that Sindh is more vulnerable to climate variabilities than other provinces. The influence of CC on rice yield in light of several carbon dioxide emission scenarios was assessed by Reference [40].…”
Section: Introductionmentioning
confidence: 99%
“…Xie et al (2013) assess the frequency of drought occurrence in Pakistan; Yang et al (2013) examine the climate sensitivity of Pakistan's rivers and agriculture sector; and Zhu et al (2013) assess alternative water-and agriculture-based climate change adaptation strategies for the country. Xie et al (2013) find that when large droughts occur in Pakistan, they affect all key agricultural areas.…”
Section: Contributions Of This Special Issuementioning
confidence: 99%
“…A large number of system models have been built for some of these basins such as Cai et al (2002) and Teasley and McKinney (2011) for Syr Darya; Jalilov et al (2013) for Amu Darya and Yu et al (2013) and Yang et al (2013) for Indus. The Ganges and the Brahmaputra have relatively fewer previous system modeling studies.…”
Section: System Modelingmentioning
confidence: 99%